RETRACTED: The Role of Tourism Destination and Human Resources in Sustainable Tourism Implementation in Indonesia - Komang Trisna Pratiwi Arcana; I Wayan Eka Sudarmawan (Journal of Business on Hospitality and Tourism, 2020)
This article has been retracted at the request of the Editor-in-Chief. It is reported that this article has been published in Journal of Business on Hospitality and Tourism Vol 5, No 2 (2019) [https://jbhost.org/jbhost/index.php/jbhost/issue/view/8]. Authors have been contacted regarding this and have admitted submitting this paper by mistake.    We apologize to readers of the journal that this was not detected during the submission process.The development of world tourism experienced a surge in tourist arrivals both international and domestic. Developments, the share of the global tourism market and new opportunities to serve the middle class is growing rapidly. The group of potential domestic tourists are expected to ensure that tourism remains a strategic sector in the national development agenda. Indonesia is very much has a very attractive tourist destination, and Bali in particular, of course, strongly felt the impact of the surge in tourist arrivals. Readiness of Tourism Human Resources are needed to support the sustainable tourism program.